Personality correlates of the self-rated frequency of erotic dreams - Schredl, Michael; Göritz, Anja (International journal of dream research, 2022)
Erotic dreams have been of interest for researchers and the public alike. Although, the gender difference in the frequency of erotic dreams is well documented with men reporting erotic dreams more often than women, studying other factors, for example, personality traits, in relationship with erotic dreaming is scarce. Overall, 1711 participant estimated the percentage of erotic dreams with regard to all their remembered dreams and also completed a Big Five Personality inventory. The findings indicate that four of the Big Five personality factors were related to the frequency of erotic dreams; although the effects sizes of these associations were small. As expected, openness to experience correlated with a higher frequency of sexual dreams, as this personality trait is related to more frequent positive sexual cognitions and pornography consumption. Whereas extraversion and neuroticism were also positively related to erotic dream frequency, agreeableness showed a negative relationship. These kinds of studies help to understand how waking life sexuality affect erotic dreams, and in more general terms, how waking life is reflected in dreams.
Gesehen am 07.04.2022